CircRNF111 Protects Against Insulin Resistance and Lipid Deposition via Regulating miR-143-3p/IGF2R Axis in Metabolic Syndrome - Lin, Xihua; Du, Ying; Lu, Weina; Gui, Weiwei; Sun, Shuiya; Zhu, Yiyi; Wang, Gangliang; Eserberg, Daniel Turunen; Zheng, Fenping; Zhou, Jiaqiang; Wu, Fang; Li, Hong (Frontiers in Cell and Developmental Biology, 2021)
As a subclass of noncoding RNAs, circular RNAs (circRNA) expression aberration has been identified in various human diseases. In this study, we investigated whether circRNAs could act as competing endogenous RNAs to regulate the pathological process-insulin resistance and dyslipidemia of Metabolic Syndrome (MetS). The profile of circRNAs in serume of MetS and control samples was characterized by circRNA deep sequencing. We identified circRNF111 as a key downregulated circRNA involved in MetS. The decreased expression of circRNF111 in the serum samples of MetS was directly associated with excessive insulin resistance and dyslipidemia. Loss-of-function experiments showed that circRNF111 knockdown inhibited the glucose uptake and the Akt signaling pathway, meanwhile increased the deposition of triglycerides in adipogenic differentiated human adipose-derived stem cells (hADSCs). Mechanistically, circRNF111 acted as a sponge of miR-143-3p and functioned through targeting miR-143-3p and its downstream target gene IGF2R. The role and mechanism of circRNF111 sponging miR-143-3p in MetS was also explored in high-fat diet induced obese mice. Taken together, our results reveal a protective role for a novel circRNA-circRNF111 in MetS progression. CircRNF111 inhibition enhances insulin resistance and lipid deposition in MetS through regulating miR-143-3p-IGF2R pathway. It provides a potentially effective therapeutic strategy for MetS progression.